Istihsan as a Finding Method of Progressive Islamic Law in the Industrial Revolution Era 4.0 - Diky Faqih Maulana; Abdul Rozak (Institut Agama Islam Negeri Palangka Raya, 2021)
The rapid development of generations and science raises various new problems that are not only solved by the legal sources of the Qur'an and Hadith. Istihsan is a way of finding Islamic law, which is used as a proposition (dalil) in Hanafi fiqh. The article examined the role of istihsan as a finding method of progressive Islamic law. The research was descriptive-analytical with a normative approach. Istihsan is another most decisive option in finding Islamic law, because many contemporary things in the era of the industrial revolution 4.0, such as eye transplant law, buying and selling without qabul lafdzi at mini markets, and transactions on vending machines and online shops have been completed using the istihsan method, as well as establishing the laws. The essential goal of istihan is to eliminate madorot (harm) and achieve maslahah (benefits). While maslahah is the goal of value in the establishment of progressive Islamic law. istihsan is very possible to be developed and modified as a method of establishing the law that is dynamically and develops following the times.